THE HISTORY OF PENETRATION OF DIGITAL TECHNOLOGY IN EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Digital technology and literacy can heighten the transformation of teaching and learning in higher education institutions. This study uncovers the extent to which digital technologies have been used to advance the teaching and learning process in higher education institutions, and the barriers and bottlenecks to why it may not have been effectively implemented across the higher education institutions. The study used selected countries based on the main focus of the educators, commercial, and financial investors; to show the level of impact/implications of computer technologies on the teaching and learning processes.